The Anglo-Saxon chronicle. Volume 7 MS E a collaborative edition - Irvine, Susan (D.S. Brewer, 2004)
Part of the Anglo-Saxon Chronicle Collaborative Series, which now includes editions of the main texts through from A to F. This volume offers a new edition of the E-text of the Anglo-Saxon Chronicle, commonly known as the Peterborough Chronicle. The E-text is of enormous importance in Chronicle studies: in its early part it is the best representativeof the Northern Recension of the Chronicle; in continuing up to the second half of the twelfth century, its span is by far the longest of all the versions. Even more than other versions of the Chronicle, it reflects transitions ofvital interest to historians, linguists, and literary scholars. The E-text has not been edited in its entirety, except as a facsimile, for over a century. This semi-diplomatic edition offers a readable text with modern punctuation and capitalization. The interpolated material relating to Peterborough is clearly distinguished from the rest of the text. Indices of personal names, people-names, and place-names follow the text itself. The Introduction includes an account of the manuscript and a linguistic analysis of the E-text. The E-text cannot of course be studied in isolation. This volume is part of the Anglo-Saxon Chronicle Collaborative Series and with its publicationthe Series now includes editions of the main texts through from A to F. A substantial section of the Introduction to the volume is devoted to a detailed discussion of E's complex textual relationships with the other versions of the Chronicle, and also with other relevant documents such as Peterborough Charters and twelfth-century Latin chronicles. Dr SUSAN IRVINE is Senior Lecturer in the Department of English, University College, London